The Influence of Domestic Learning Environment on Students' Learning Motivation - Ahmad Bahrul Arifin; Mohammad Fadil (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
Learning motivation is a crucial determinant influencing student engagement in the overall learning process. This study aimed to investigate the influence of the home learning environment on students' learning motivation at MTs Nasruddin Dampit. A quantitative approach with a correlational design was employed. Data were collected using a questionnaire developed based on the indicators of each variable, and subsequently analyzed using simple linear regression with IBM SPSS Statistics version 29.0. The results of the analysis revealed a significance value of 0.001 (α < 0.05), indicating that the home learning environment has a significant influence on students' learning motivation. The resulting regression equation, Y = 39.27 + 0.43X, indicates that an increase in the quality of the home learning environment is followed by an increase in students' learning motivation. These findings affirm that the availability of learning facilities, a supportive family relationship, and continuous emotional support are fundamental elements in building learning motivation and supporting students' academic success.